Synthesis of Graphene from Pencils Graphite Via Electrochemical Exfoliation Method as a Cu-Foil Coating on the Anode-Free Lithium-Ion Battery - Neka Nur Aida; Muhammad Ikhsanudin; Anafi Nur'aini; Eka Lutfi Septiani; Anif Jamaludin; Hendri Widiyandari (ALCHEMY Jurnal Penelitian Kimia, 2024)
The Anode-free Li-ion Battery (AFLB) is an alternative to a new Li-ion battery model that offers high energy density at the same battery size as conventional models. Uncontrolled dendrite growth inactive the lithium deposition, resulting in decreased specific capacity, shortened lifecycle, and reduced coulombic efficiency. This work reported the utilization of graphene derived from pencil graphite for coating Cu foil as a current collector in AFLBs, to mitigate the formation of lithium dendrites and enhance battery capacity. The graphene-coated Cu foil exhibits a specific capacity of 143 mAh/g, representing a 20 mAh/g increase compared to batteries lacking a graphene coating. The coulombic efficiency of the battery with graphene coating in the charging and discharging process for three cycles is 84.53% in the 1st cycle, 101.44% in the 2nd cycle, and 98.58% in the 3rd cycle.